Analysis of Factors Affecting Least-Cost Size of Plant - Babb, E. M.; Yu, T. H. (Management Science, 1970)
A general model used to analyze the effects of assembly and distribution factors and economies of scale in processing on least-cost size of plant and on cost components is described. This model is applied to empirical data from fluid milk plants and country elevators. In both cases, it appears that total per unit cost (combined assembly, processing and distribution cost) is a continuously falling function of plant size, at least to the limit of observed plant sizes. In the two cases studied, the larger plants observed appeared to have from 20 to 30 percent lower cost than plants of average size. The results of these two applications indicate the basis for much of the current consolidation of plants.